Clerodendrum japonicum (Thunb.) Sweet leaf extract supported nanosilver particles: Characterization, antioxidant and antibacterial activity - Rabha, Deepak; Sarma, Himangshu; Borah, Manjit; Ghose, Vivek; Barman, Dharmeswar; Rao, Someswar; Sarma, Hemanta Kumar; Devi, Rajlakshmi; Boruah, Dulal Chandra (Vietnam Journal of Science and Technology, 2024)
Silver nanoparticles have been synthesized in numerous ways, due to their diverse applications, including green procedures that used an extract of plants for the reduction of metal ions. This study delineates the green synthesis and characterization of silver nanoparticles (AgNPs) from the leaf extract of Clerodendrum japonicum (Thunb.) Sweet (CJ) and assesses the antioxidant as well as antibacterial characteristics. The biosynthesis of AgNPs was accomplished by reacting the aqueous leaf extract of the plant with a solution of silver nitrate (AgNO3). The creation of AgNPs was indicated by the visual colour change of the reaction concoction from golden to deep brown and the absorption peak at 442 nanometer (nm) in the ultraviolet-visible spectroscopy. The Field Emission Scanning Electron Microscope (FESEM) and the High-Resolution Transmission Electron Microscope (HRTEM) images have revealed the generated AgNPs as spherical and oblate in shape which is 20-40 nm in size, whereas X-Ray power Diffraction evaluation revealed the crystalline feature. The existence of functional groups of synthesized AgNPs was detected by the Fourier Transform Infra-Red (FTIR) spectrum. The synthesized AgNPs showed free radical scavenging activity using 2, 2-Diphenyl-1-picryl hydrazyl assay with IC50 value, 7.02±1 μg/mL. The antibacterial assay showed an effective activity towards E. Coli and S. aureus by developing a well-defined zone of inhibition. The results of this study accentuate the biomedical potential of the above-mentioned plant, though further research is needed to implement it in clinical practice.